On rational functions of the best nonsymmetric approximations in integral metrics - Polyakov, O. V.; Ruchaevskaya, N. O. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain theorems that characterize the degree of the rational function of the best (α, β) -approximation in the space L_p and conditions under which the value of the best rational (α, β) -approximation is less than the best (α, β) -approximation by algebraic polynomials.